Nuclear spin conversion of water inside fullerene cages detected by low-temperature nuclear magnetic resonance - Mamone, Salvatore; Concistre, Maria; Carignani, Elisa; Meier, Benno; Krachmalnicoff, Andrea; Johannessen, Ole G.; Lei, Xuegong; Li, Yongjun; Denning, Mark; Carravetta, Marina; Goh, Kelvin; Horsewill, Anthony J.; et al. (American Institute of Physics, 2014)
The water-endofullerene H2O@C60 provides a unique chemical system in which freely rotating water molecules are confined inside homogeneous and symmetrical carbon cages. The spin conversion between the ortho and para species of the endohedral H2O was studied in the solid phase by low-temperature nuclear magnetic resonance. The experimental data are consistent with a second-order kinetics, indicating a bimolecular spin conversion process. Numerical simulations suggest the simultaneous presence of a spin di↵usion process allowing neighbouring ortho and para molecules to exchange their angular momenta. Cross-polarization experiments found no evidence that the spin conversion of the endohedral H2O molecules is catalysed by 13C nuclei present in the cages.